Will China’s demographic transition exacerbate its income inequality? A CGE modeling with top-down microsimulation - Wang, Xinxin; Chen, Kevin Z.; Robinson, Sherman; Huang, Zuhui (International Food Policy Research Institute, 2016)
Demographic transition due to population aging is an emerging trend throughout the developing world, and it is especially acute in China, which has undergone demographic transition more rapidly than have most industrial economies. This paper quantifies the distributional effects in the context of demographic transition using an integrated recursive dynamic computable general equilibrium model with top-down behavioral microsimulation. The results of the poverty and inequality index indicate that population aging has a negative impact on the reduction of poverty while its impact is positive with regard to equality. In addition, elderly rural households are experiencing the most serious poverty, and their inequality problems compared with other household groups and within group inequality worsens with demographic transition. These findings not only advance the previous literature but also deserve particular attention from Chinese policy makers.